2020
DOI: 10.3390/ijerph17041290
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drink Consumption, Depression, and Salutogenic Sense of Coherence Among Adolescents and Young Adults

Abstract: The prevalence of energy drink consumption has increased in Hungary over the past 10–15 years. This study assesses the frequency, motivations, and adverse effects of energy drink consumption, and examines how the process of becoming a regular consumer is connected with sense of coherence and depression symptoms. A total of 631 high school and college students were assessed using the Depression Scale (BDS-13) and Sense of Coherence Scale (SOC-13). Logistic regression models were fit to test the effect of and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 42 publications
8
30
0
4
Order By: Relevance
“…The latter is in accordance with a study conducted in the USA [13,23], where it was 10% in college students aged 18 years [23]. A recent study showed that consumption of EDs can be associated with substance use such as cigarette smoking, binge drinking and opioid use among middle and high school students [24]. In young people, the primary side effects of consuming EDs include tachycardia, insomnia and tremors [25].…”
Section: Discussionsupporting
confidence: 86%
“…The latter is in accordance with a study conducted in the USA [13,23], where it was 10% in college students aged 18 years [23]. A recent study showed that consumption of EDs can be associated with substance use such as cigarette smoking, binge drinking and opioid use among middle and high school students [24]. In young people, the primary side effects of consuming EDs include tachycardia, insomnia and tremors [25].…”
Section: Discussionsupporting
confidence: 86%
“…As shaking hands is the one of the most common side effects [ 60 ], it may exert a negative effect on the final outcome in sport disciplines where precision is required. On the other hand, a study where an association between ED consumption and mental problems was investigated presented that young people who ingested EDs and were engaged in physical activity reported less symptoms of depression [ 75 ]. Similar findings were observed in previously mentioned studies where none of subjects experienced any mental side effect [ 53 , 57 , 58 ].…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
“…Additionally, the study using analysis of structural equation modeling found that SES was associated with adolescent depressive symptoms indirectly through maternal care separately, as well as through maternal care and adolescent SOC sequentially [ 37 ]. Furthermore, a recent study found that adolescents with a weaker sense of coherence and a tendency toward depression were much more likely to become addicted to energy drinks, while a strong sense of coherence diminishes the effects of depression [ 20 ]. Mental health complaints have also shown to commonly co-occur and highly correlate with somatic health complaints (reoccurring pains and aches) in adolescent population studies [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literatures sources indicate that symptoms of depression were frequent in adolescents and were associated with unhealthy lifestyle factors such as low physical activity [ 42 ]. Other research finding suggest that exercise may help to mitigate symptoms of depression by reducing inflammation [ 21 ] and those adolescents that were active in sports were significantly less likely to report symptoms of depression [ 20 ]. We investigated gender differences in depressive symptoms among adolescents and found that girls are affected twice as often as boys (β = −0.056, p < 0.001) and our findings coincide with literature data [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation